Prevalence and Clinical Factors of Migraine in Patients With Spontaneous Coronary Artery Dissection - Susan N. Kok; Sharonne N. Hayes; F. Michael Cutrer; Claire E. Raphael; Rajiv Gulati; Patricia J.M. Best; Marysia S. Tweet (2018)
Background Spontaneous coronary artery dissection (SCAD) is a cause of acute coronary syndrome predominantly in women without usual cardiovascular risk factors. Many have a history of migraine headaches, but this association is poorly understood. This study aimed to determine migraine prevalence among SCAD patients and assess differences in clinical factors based on migraine history. Methods and Results A cohort study was conducted using the Mayo Clinic SCAD “Virtual” Multi‐Center Registry composed of patients with SCAD as confirmed on coronary angiography. Participant‐provided data and records were reviewed for migraine history, risk factors, SCAD details, therapies, and outcomes. Among 585 patients (96% women), 236 had migraine history; the lifetime and 1‐year prevalence of migraine were 40% and 26%, respectively. Migraine was more common in SCAD women than comparable literature‐reported female populations (42% versus 24%, P <0.0001; 42% versus 33%, P <0.0001). Among all SCAD patients, those with migraine history were more likely to be female (99.6% versus 94%; P =0.0002); have SCAD at a younger age (45.2±9.0 years versus 47.6±9.9 years; P =0.0027); have depression (27% versus 17%; P =0.025); have recurrent post‐SCAD chest pain at 1 month (50% versus 39%; P =0.035); and, among those assessed, have aneurysms, pseudoaneurysms, or dissections (28% versus 18%; P =0.018). There was no difference in recurrent SCAD at 5 years for those with versus without migraine (15% versus 19%; P =0.39). Conclusions Many SCAD patients have a history of migraine. SCAD patients with migraine are younger at the time of SCAD; have more aneurysms, pseudoaneurysms, and dissections among those imaged; and more often report a history of depression and post‐SCAD chest pain. Clinical Trial Registration URL: https://www.clinicaltrials.gov . Unique identifiers: NCT01429727, NCT01427179.